(3QDjI CHh ESeGYjd GdMSjf Hf Ydi Hf eMeO GdWZQGFis - (3GdMSjf Hf Ydj Hf eMeO Hf YHO GdUeO, CHh ESeGYjd, eDjO GdOjf, GdCUHgGfj GdWZQGFj,J (B513 (3g` s
(3ChdgG (B:s
(3bGd QCjJ ai GdSfI GdJi cfJ ajgG ai TgQ QeVGf hbO cGf gfGc cJGH GdQMeI dLGHQ Hf MjGf hcfJ CJCedg hdG Cba Ydi eYGfjg s
(3BNQgG (B:s
(3hGMce GdfGS ai UfGYJg ef GbJOi HGdeUhQ GdHGQi hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3Jdjg bUjOI deMeO Hf Cejd hcJGH HGdaGQSjIs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs